Petrological, geochemical (major, trace, and rare earth elements), and U–Pb zircon data of the Tamatán Group, NE Mexico - Casas Peña, Juan Moisés; Ramírez Fernández, Juan Alonso; Velasco Tapia, Fernando; Alemán Gallardo, Eduardo Alejandro; Augustsson, Carita; Weber, Bodo; Frei, Dirk; Jenchen, Uwe (Elsevier, 2021)
From samples of the Paleozoic Tamatán Group (Huizachal–Peregrina Anticlinorium, Tamaulipas, Mexico), petrographic (qualitative and modal) and geochemical analyses (major, trace, and rare earth elements) were conducted. The first U–Pb geochronological data on detrital zircons of the Tamatán Group were generated using four samples. The data presented here contains a broad overview of photomicrography, recalculated modal point-count data, raw geochemical data, and simple statistics of selected geochemical parameters. The data presented in this article are interpreted and discussed in the research article titled “Provenance and tectonic setting of the Tamatán Paleozoic sequence, NE Mexico: Implications for the closure of the Rheic Ocean at the northwestern part of Gondwana” [1].